Effect of Water Stress on Morphological Characteristics of Vachellia tortilis (Forssk.) Galasso & Banfi, Vachellia nilotica (L.) P.J.H.Hurter & Mabb. and Senegalia senegal (L.) Britton Seedlings in Maiduguri, Nigeria - Mali Bulama, Gubio; Mohammad, Saquib (Nepal Journal of Botany, 2025)
This study investigated the effect of water stress on three species Vachellia tortilis (Forssk.) Galasso & Banfi, Vachellia nilotica (L.) P.J.H.Hurter & Mabb., and Senegalia Senegal (L.) Britton to varying degrees of water stress in Maiduguri, Borno State, Nigeria. The experiment assessed key morphological parameters such as shoot length, root length, shoot and root dry weights, total dry matter, and root-to-shoot ratio at 60, 90, and 120 days after sowing. A split-plot design was employed with four watering regimes: control (M0), slight (M1), moderate (M2), and severe moisture stress (M3). The results revealed significant interspecific differences in growth responses under water stress, with S. senegal exhibiting superior shoot biomass across treatments, while V. tortilis showed the highest root-to-shoot ratio, especially under severe stress. These adaptive morphological traits highlight the species’ resilience strategies in arid and semi-arid ecosystems. The findings have implications for afforestation and agroforestry programs in drought-prone areas. These findings suggest Senegalia senegal may be better adapted to arid environments.